Patients' intention to speak up for health care providers' hand hygiene in inpatient diabetic foot wound treatment: a cross-sectional survey in diabetes outpatient centres in Lower Saxony, Germany*. Issue 10 (26th November 2017) - von Lengerke, Thomas; Kröning, Barbara; Lange, Karin
Abstract: Hand hygiene in wound care by health care providers (HCPs) is a key principle in treating hospitalized patients with diabetic foot infections. This study aimed to estimate the extent to which patients with type-2-diabetes (T2D) intend to speak up for HCPs' hand hygiene during inpatient foot treatment, test whether this motivation increases given the hospital would invite patients to speak up, and identify associations with socio-demographics, knowledge of hand hygiene requirements, and diabetes-related factors. A questionnaire-survey was conducted in eight diabetes outpatient centres in Lower Saxony/Germany. Intentions to speak up (without and with institutional encouragement) and knowledge about hand hygiene during foot-care were assessed. Analyses of variance were conducted, partly as repeated measures-models with intention-items as within-subject factor. N  = 473 patients participated (response = 77.4%). N  = 177 (41%) strongly intended to speak up. Institutional encouragement was associated with an increased rate of strong (54% vs. 41%; p  < .001) and higher mean intention ( M  = 3.9 vs. 3.4 with vs. without encouragement [5-point-scales]; F (1, 434) = 41.5, p  < .001). In patients without diabetic foot syndrome, this effect was limited to those with at least medium school education ( F (2, 292) = 4.4, p  = .013) and knowledge on HCPs' hand hygiene ( F (2, 294) = 3.1, p  = .047). In conclusion, a majority of T2D-patients in diabetes outpatient centres intend to speak for HCPs' hand hygiene in inpatient foot treatment, and are receptive to institutional encouragement. However, this presupposes at least medium education and knowledge about hand hygiene, emphasizing that patient empowerment begins with knowledge.